Managing healthcare employees' burnout through micro aspects of corporate social responsibility: A public health perspective - Chen, Rongxin; Liu, Wei (Frontiers in Public Health, 2023)
Background Globally, an increasing number of healthcare workers (HCW) suffer from the issue of burnout (BO) annually. The critical issue of BO undermines the capacity of HCW to deliver superior healthcare services on the one end, it negatively affects the mental health of HCW on the other hand. Although HCW in developed and developing countries face the risk of BO, however, this issue is more critical in developing countries due to poor infrastructure, resources and social inequalities. The BO syndrome has recently been recognized as a public health concern, and new approaches are required to manage this epic, especially in healthcare management, effectively. In this respect, past research recognizes the role of corporate social responsibility (CSR) in influencing employee outcomes. Especially the micro aspects of CSR (MCSR) have recently received growing attention from academicians and practitioners. However, most existing MCSR investigations relate to the positive aspects of individual psychology, leaving the terrain unattended on how MCSR can help employees in reducing negative work outcomes for example, BO. To close this critical gap, the basic aim of this study is to investigate the relationship between MCSR and BO. Further, to understand the underlying mechanism of how and why MCSR may reduce employees' BO, this study introduces two mediators, work engagement (WE) and intrinsic motivation (IM) and one moderator, compassion at work (CW). Method The data for the current study were gathered randomly from HCW serving in different hospitals of a developing country. Specifically, we collected the data in three separate waves. A self-administered questionnaire was used as a data collection instrument by following a paper-pencil methodology. The response rate in this study remained close to 64%. Both male and female HCW participated in this study. We validated the hypothesized relationships with the help of structural equation modeling in AMOS software. Results The results confirmed that MCSR negatively predicts BO, and WE and IM mediated this relationship. Moreover, the moderating effect of CW was also confirmed. Conclusion The findings of this study help healthcare administrators to mitigate the epic of BO among HCW by carefully planning and executing MCSR policies.